2006
DOI: 10.1016/j.jfms.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics of feral cats admitted to seven trap-neuter-return programs in the United States

Abstract: Internationally, large populations of feral cats constitute an important and controversial issue due to their impact on cat overpopulation, animal welfare, public health, and the environment, and to disagreement about what are the best methods for their control. Trap-neuter-return (TNR) programs are an increasingly popular alternative to mass euthanasia. The objective of this study was to determine the population characteristics of feral cats admitted to large-scale TNR programs from geographically diverse loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 16 publications
2
69
0
1
Order By: Relevance
“…Even when the common overrepresentation of female cats in shelters (Lepper et al 2002;Wallace and Levy 2006;Alberthsen et al 2016) is considered, the female to male sex ratio among dead cats was greater in comparison with the sex ratio of cats admitted to the monitored shelters. Considering the mortality rate and median LOS, our results suggest that females are admitted to shelters in a worse condition than males and that males have a higher survival rate.…”
Section: Discussionmentioning
confidence: 94%
“…Even when the common overrepresentation of female cats in shelters (Lepper et al 2002;Wallace and Levy 2006;Alberthsen et al 2016) is considered, the female to male sex ratio among dead cats was greater in comparison with the sex ratio of cats admitted to the monitored shelters. Considering the mortality rate and median LOS, our results suggest that females are admitted to shelters in a worse condition than males and that males have a higher survival rate.…”
Section: Discussionmentioning
confidence: 94%
“…28 Such data may be characterized according to program type, veterinarian, animal species, surgery type, or other criteria to aid in identification of risk factors and inform subsequent refinement of protocols. 268,269 As in any veterinary practice, recognizing patterns is crucial to reducing morbidity and mortality rates, because pattern detection alerts the healthcare team to areas where the likelihood of complications is greatest so that protocols can be improved and vigilance increased at critical points. [270][271][272] High-quality, high-volume spayneuter programs can achieve morbidity and mortality rates similar to or lower than those encountered in small animal general practice.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The female domestic cat clearly and consistently displays seasonal reproductive activity with increasing northern latitudes (Jemmett & Evans 1977, Hurni 1981, Spindler & Wildt 1999, Freistedt et al 2001, Comizzoli et al 2003, Wallace & Levy 2006. In general, the nonbreeding (NB) season for free-living North American cat populations occurs over a 4 mo interval (Jemmett & Evans 1977), usually involving the months from August through January (Jemmett & Evans 1977, Spindler & Wildt 1999, Comizzoli et al 2003, Wallace & Levy 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the nonbreeding (NB) season for free-living North American cat populations occurs over a 4 mo interval (Jemmett & Evans 1977), usually involving the months from August through January (Jemmett & Evans 1977, Spindler & Wildt 1999, Comizzoli et al 2003, Wallace & Levy 2006. Previous studies have revealed that circulating gonadotropins, estrual activity, and pregnancy success decline in response to decreased photoperiod (Leyva et al 1989, Jochle & Jochle 1993, Wallace & Levy 2006.…”
Section: Introductionmentioning
confidence: 99%